Characterization of Hepatozoon spp. in Leptodactylus chaquensis and Leptodactylus podicipinus from two regions of the Pantanal, state of Mato Grosso do Sul, Brazil - Menezes Leal, Denise Dutra [UNESP]; Dreyer, Carine Spenassatto [UNESP]; Silva, Reinaldo Jose da [UNESP]; Martins Ribolla, Paulo Eduardo [UNESP]; Paduan, Karina dos Santos [UNESP]; Bianchi, Inacio [UNESP]; O'Dwyer, Lucia Helena [UNESP] (Springer, 2015)
Hepatozoon sp. are parasites that commonly infect frogs and arthropod vectors. This species has variability in the morphological and morphometric characteristics. Due to these variations, the naming of the species is thus impaired and only by visualizing the sporogonic cycle in vector and by molecular studies this problem can be solved. Recently, the use of molecular genetics has helped the species denomination. In this work, we collected 145 frogs (68 Leptodactylus chaquensis and 77 Leptodactylus podicipinus) in different sampling sites, where were found 18 (26.47 %) L. chaquensis and 24 (31.17 %) L. podicipinus parasitized; besides of gamonts, schizogonic forms were also seen in animals organs. The positivity difference between the collection sites for both frog species was not significant (p=0.958). Comparing gamonts found in each species of anuran, we observed differences in morphology. The comparison in the molecular level for L. podicipinus was not possible due to small amount of blood obtained, just L. chaquensis had their parasites DNA sequenced. The amplified and sequenced samples, named HEP1 to HEP10, are presented in the phylogenetic tree as a different branch from other haemogregarines described on other hosts. Therefore, we have seen that, although the morphology and morphometry of the collected parasites at each site showed differences, the sequencing of these samples revealed identical species of Hepatozoon, and different compared to those from GenBank, thereby demonstrating that the species of Hepatozoon in L. chaquensis observed in this study probably represent a new species.
Keywords: Leptodactylidae; Hepatozoon sp; Frogs; Leptodactylus chaquensis; Leptodactylus podicipinus